Shaping a sustainable future: Bibliometric analysis of vocational education curricula aligned with the SDGs - Latif, Muh Abdul; Widiaty, Isma; Abdullah, Ade Gafar (Research and Social Study Institute, 2024)
The preparation of SDGs-based vocational education curriculum needs to be prepared. The first step is how this context is discussed globally. This study aims to see how research trends related to vocational education curriculum are in line with the achievement of SDGs. Bibliometric analysis is used to explore information related to these trends. The scope of the research is reviewed based on the year of publication, the most productive countries, documents with the most citations and co-occurrence analysis. This analysis uses the Scopus database as a data source then uses VosViewer to analyze co-citations and co-occurrence. The results obtained were 1041 relevant documents with a period spanning 2015 to February 2024. Based on the year of publication, the topics that examine this theme have significantly increased, then the countries that contribute the most are mostly developed countries such as the United States, England and Spain which are concerned with discussing this theme. Then from the average most citations are in journals published in 2020 which dominate. The co-occurrence results obtained 4 interrelated thematic clusters, namely the relationship between SDGs and education, curriculum, learning models, competencies, technology, educational transformation of the industrial revolution 4.0 and green industry. The implications of this study as a reference for curriculum developers, especially in vocational education which must develop in accordance with the demands of the development of the world of work. This study contributes to increasing insight for researchers who pay attention to themes related to the SDGs-based vocational education curriculum. In addition, it can be used by stakeholders as a reference in preparing the integration of sustainable education in vocational education.